Advances in CRISPR/Cas9-based research related to soybean [Glycine max (Linn.) Merr] molecular breeding - Yao, Dan; Zhou, Junming; Zhang, Aijing; Wang, Jiaxin; Liu, Yixuan; Wang, Lixue; Pi, Wenxuan; Li, Zihao; Yue, Wenjun; Cai, Jinliang; Liu, Huijing; Hao, Wenyuan; et al. (Frontiers in Plant Science, 2023)
Soybean [Glycine max (Linn.) Merr] is a source of plant-based proteins and an essential oilseed crop and industrial raw material. The increase in the demand for soybeans due to societal changes has coincided with the increase in the breeding of soybean varieties with enhanced traits. Earlier gene editing technologies involved zinc finger nucleases and transcription activator-like effector nucleases, but the third-generation gene editing technology uses clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9). The rapid development of CRISPR/Cas9 technology has made it one of the most effective, straightforward, affordable, and user-friendly technologies for targeted gene editing. This review summarizes the application of CRISPR/Cas9 technology in soybean molecular breeding. More specifically, it provides an overview of the genes that have been targeted, the type of editing that occurs, the mechanism of action, and the efficiency of gene editing. Furthermore, suggestions for enhancing and accelerating the molecular breeding of novel soybean varieties with ideal traits (e.g., high yield, high quality, and durable disease resistance) are included.